2013
DOI: 10.1371/journal.pone.0076569
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the Transcriptome of Sulfolobus acidocaldarius by Exoribonuclease aCPSF2

Abstract: Recent studies identified a 5´ to 3´ exoribonuclease termed Sso-RNase J in the crenarchaeon Sulfolobus solfataricus (Sso), which has been reclassified to the aCPSF2 (archaeal cleavage and polyadenylation specificity factor 2) group of β-CASP proteins. In this study, the Sso-aCPSF2 orthologue of Sulfolobus acidocaldarius (Saci-aCPSF2) was functionally characterized. Like Sso-aCPSF2, Saci-aCPSF2 degrades RNA with 5´ to 3´ directionality in vitro. To address the biological significance of Saci-aCPSF2, a deletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Crystal structures were solved for aCPSF1 variants from three different archaea, Pyrococcus horikoshii , Methanosarcina mazei , and Methanothermobacter thermautotrophicus , revealing a tripartite structure that enables exoribonucleolytic activity with 5ʹ monophosphorylated (5ʹp) RNA substrates . In S. solfataricus , Sso‐aCPSF2 was demonstrated to act as a 5ʹ to 3ʹ exonuclease with a preference for RNA molecules with 5ʹp ends over RNAs with 5ʹppp termini . The translation initiation factor a/eIF2 can bind mRNAs with 5ʹppp ends (but not RNAs with 5ʹp or 5ʹpp ends) to provide protection from Sso‐aCPSF2 degradation, and in vivo experiments showed that the overproduction of a/eIF2(γ) increases the stability of different mRNAs .…”
Section: ʹ Rna Termini and Possible Capping Mechanismsmentioning
confidence: 99%
“…Crystal structures were solved for aCPSF1 variants from three different archaea, Pyrococcus horikoshii , Methanosarcina mazei , and Methanothermobacter thermautotrophicus , revealing a tripartite structure that enables exoribonucleolytic activity with 5ʹ monophosphorylated (5ʹp) RNA substrates . In S. solfataricus , Sso‐aCPSF2 was demonstrated to act as a 5ʹ to 3ʹ exonuclease with a preference for RNA molecules with 5ʹp ends over RNAs with 5ʹppp termini . The translation initiation factor a/eIF2 can bind mRNAs with 5ʹppp ends (but not RNAs with 5ʹp or 5ʹpp ends) to provide protection from Sso‐aCPSF2 degradation, and in vivo experiments showed that the overproduction of a/eIF2(γ) increases the stability of different mRNAs .…”
Section: ʹ Rna Termini and Possible Capping Mechanismsmentioning
confidence: 99%
“…We have put forward a model specifying that either trimeric SsoIF2 or SsoIF2γ alone binds to the 5′-terminal end of mRNAs and protects them from 5′ to 3′ directional decay during nutrient limitation, for example, when they grow chemolithotrophically [12]. This hypothesis was supported by the discovery of the S. solfataricus RNase aCPSF2 displaying 5′-to-3′ directional mRNA decay, which was shown to be impeded in vitro by SsoIF2γ bound to the 5′-terminal triphosphate end of RNA substrates [24,25]. This would result in 5′-end protection of the respective mRNAs under conditions when translation is decreased.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…This is in contrast to B. subtilis , where under severe depletion conditions of RNase J1 roughly 30% of all mRNAs were affected 21 . Just recently an RNA-seq approach with the Crenarchaeon Sulfolobus acidocaldarius revealed global alterations of the transcriptome by deletion of aCPSF2 an archaeal homolog of RNase J 37 . The identification of RNA fragments exclusively accumulating in the RNase J deletion strain 2.4.1∆ rnj and virtually not detectable in the wild type leads to a number of questions regarding different aspects of RNA metabolism.…”
Section: Discussionmentioning
confidence: 96%